High indirect bilirubin levels as an independent predictor of postoperative myasthenic crisis: a single-center, retrospective study - Sun, Chao; Ruan, Zhe; Zhang, Yu; Guo, Rongjing; Li, Huanhuan; Wang, Tantan; Gao, Ting; Tang, Yonglan; Song, Na; Hao, Sijia; Huang, Xiaoxi; Li, Shuang; et al. (Frontiers in Neurology, 2024)
Background Thymectomy is an efficient and standard treatment strategy for patients with myasthenia gravis (MG), postoperative myasthenic crisis (POMC) is the major complication related to thymectomy and has a strongly life-threatening effect. As a biomarker, whether the bilirubin level is a risk factor for MG progression remains unclear. This study aimed to investigate the association between the preoperative bilirubin level and postoperative myasthenic crisis (POMC). Methods We analyzed 375 patients with MG who underwent thymectomy at Tangdu Hospital between January 2012 and September 2021. The primary outcome measurement was POMC. The association between POMC and bilirubin level was analyzed by restricted cubic spline (RCS). Indirect bilirubin (IBIL) was divided into two subgroups based on the normal upper limit of IBIL, 14 μmol/L. Results Compared with non–POMC group, IBIL levels were significantly higher in patients with POMC. Elevated IBIL levels were closely associated with an increased risk of POMC (p for trend = 0.002). There was a dose-response curve relationship between IBIL levels and POMC incidence (p for non–linearity = 0.93). However, DBIL levels showed a U-shaped association with POMC incidence. High IBIL level (≥14 μmol/L) was an independent predictive factor for POMC [odds ratio = 3.47, 95% confidence interval (CI): 1.56–7.8, p = 0.002]. The addition of high IBIL levels improved the prediction model performance (net reclassification index = 0.186, 95% CI: 0.039–0.334; integrated discrimination improvement = 0.0345, 95% CI: 0.005–0.065). Conclusion High preoperative IBIL levels, especially those exceeding the normal upper limit, could independently predict the incidence of POMC.